Pre-existing type 2 diabetes and risk of lung cancer: a report from two prospective cohort studies of 133 024 Chinese adults in urban Shanghai. Issue 7 (3rd July 2014) - Yang, Wan-Shui; Yang, Yang; Yang, Gong; Chow, Wong-Ho; Li, Hong-Lan; Gao, Yu-Tang; Ji, Bu-Tian; Rothman, Nat; Zheng, Wei; Shu, Xiao-Ou; Xiang, Yong-Bing
Abstract : Objectives: Observational studies of type 2 diabetes (T2D) and lung cancer risk are limited and controversial. We thus examined the association between T2D and risk of incident lung cancer using a cohort design. Setting: Data from two ongoing population-based cohorts (the Shanghai Men's Health Study, SMHS, 2002–2006 and the Shanghai Women's Health Study, SWHS, 1996–2000) were used. Cox proportional-hazards regression models with T2D as a time-varying exposure were modelled to estimate HRs and 95% CIs. Participants: The study population included 61 491 male participants aged 40–74 years from SMHS and 74 941 female participants aged 40–70 years from SWHS. Outcome measure: Lung cancer cases were identified through annual record linkage to the Shanghai Cancer Registry and Shanghai Municipal Registry of Vital Statistics, and were further verified through home visits and a review of medical charts by clinical and/or pathological experts. Outcome data until 31 December 2010 for men and women were used for the present analysis. Results: After a median follow-up of 6.3 years for SMHS and 12.2 years for SWHS, incident lung cancer cases were detected in 492 men and 525 women. A null association between T2D and lung cancer risk was observed in men (HR=0.87, 95% CI 0.62 to 1.21) and women (HR=0.92, 95% CI 0.69 to 1.24) after adjustments for potential confounders. Similar results were observed among never smokers. Conclusions: There is little evidence that pre-existing T2D may influence the incidence of lung cancer.